Pertumbuhan dan produksi tomat (Lycopersicum esculentum) akibat berbagai jenis pupuk organik dan dosis mulsa sekam padi - Yuniar Rizky Suryani; Adriani Darmawati Sudarma; Sumarsono Sumarsono (Department of Biology, Faculty of Sciences and Mathematics, Universitas Diponegoro, 2020)
This research aimed to identify the effect of various types of organic fertilizer and dosage of rice husk mulch on growth and production of tomato (Lycopersicum esculentum). The research used factorials 3 x 3 experiment with Completely Randomized Design (CRD) and 3 replications. The first treatment was various types of organic fertilizer such as P1: Compost, P2: Cow Manure, and P3: Goat Manure. The second treatment was dosage of rice husk mulch such as M0: Without Mulch, M1: 5 tons/ha, and M2: 10 tons/ha. The observed parameters were plant height, age of flowering, diameter of fruit, number of fruits per plant, fruit weight per plot and P uptake of plant. The result showed that the treatment effect of various types of organic fertilizer had a significant (P<0,05) on plant height. Interaction effect between various types of organic fertilizer and dosage of rice husk mulk had a significant (P<0,05) on diameter of fruit and fruit weight per plot. Compost produces the highest response to plant height. The highest response on parameter diameter of fruit on the cow manure without mulch. The goat manure with 5 tons/ha of mulch produces the highest response to weight fruit per plot.